Regulation of iron metabolism in Hamp-/-mice in response to iron-deficient diet - Patarabutr Masaratana (2018)
Background: Hepcidin, the liver-secreted iron regulatory peptide, maintains systemic iron homeostasis in response to several stimuli including dietary iron levels and body iron status. In addition, iron metabolism is controlled by several local regulatory mechanisms including IRP and Hif-2α activities independently of hepcidin. However, the roles of these mechanisms and their interaction particularly in hepcidin-deficient individuals are not yet fully understood. We, therefore, aimed to explore whether Hamp disruption affects iron homeostatic responses to dietary iron deficiency. Methods: Hepcidin1 knockout (Hamp-/-) mice and heterozygous littermates were fed with control or iron-deficient diet for 2 weeks. The expression of iron-related genes and proteins were determined by quantitative PCR and Western blot, respectively. Results: Two-week iron-deficient diet feeding in Hamp-/-mice did not alter serum iron but significantly reduced liver non-heme iron levels. This was also associated with increased ferroportin protein expression in the duodenum and spleen, whereas decreased expression was found in the liver. In addition, significant inductive effects of iron-deficient diet on Dcytb and DMT1 mRNA expression in the duodenum were noted with more pronounced effects in Hamp-/-mice compared with controls. Conclusions: Hamp-/-mice exhibited a more dramatic increase in the expression of iron transport machinery, which may be responsible for the unaltered serum iron levels upon iron-deficient diet feeding in these mice. Despite the lack of hepcidin, Hamp-/-mice can maintain a degree of iron homeostasis in response to altered dietary iron through several hepcidin-independent mechanisms. © 2012 Springer-Verlag.